Atividade antifúngica de cepas de bactérias láticas e extratos de abacaxi (Ananas comosus (L.) Merril) sobre Fusarium guttiforme Nirenberg & O’Donnell - Mamédio, Ilana Maciel Paulo (2017)
Pineapple is a tropical fruit of great commercial value, Brazil is the second largest producer of pineapple in the world. The most produced variety in the country is the “Perola”, followed by Smooth Cayenne and, both have a high degree of sus-ceptibility to fusariosis or pineapple gum disease, caused by the fungus Fusarium guttiforme.Once installed, this disease can reduce pineapple yield by up to 80%. Lactic bacteria (BAL) have their metabolic characteristics and the potential to inhibit bacterial and fungal growth, as well as to neutralize toxins produced by F. guttiforme.This work aimed to determine by in vitro tests the inhibitory effect of lactic acid bacteria on the etiologic agent of fusariosis. Qualitative and quantitative microbial inhibition tests were performed, comparing strains of lactic acid bacteria and crude pineapple extract against F. guttiforme isolates. Determination of mycotoxins in the fungal extracts of these isolates. The inhibitory effect of Lactobacillus plantarum Abx3 and Lactobacillus paracasei subsp.paracasei Abx5.2 was observed for isolateson F. guttiforme, the same did not occur with crude pineapple extract, and mycotoxin production was not detected in extracts of fungal isolates. The preliminary results of this work point out that lactic bacteria present potential to be used as a biocontrol product on F. guttiforme.